2019
DOI: 10.1002/bies.201800245
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Glioma: From Diagnosis to Therapy

Abstract: Increasing evidence indicates that extracellular vesicles (EVs) secreted from tumor cells play a key role in the overall progression of the disease state. EVs such as exosomes are secreted by a wide variety of cells and transport a varied population of proteins, lipids, DNA, and RNA species within the body. Gliomas constitute a significant proportion of all primary brain tumors and majority of brain malignancies. Glioblastoma multiforme (GBM) represents grade IV glioma and is associated with very poor prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 104 publications
0
48
0
Order By: Relevance
“…material collection 31 . Exos have attracted much attention in the diagnosis and treatment of GBM 32 . Several studies have shown that CSF Exo-encapsulated miRNAs can be used to appropriately assess the potential molecular genetic status, drug resistance and prognosis of GBM [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…material collection 31 . Exos have attracted much attention in the diagnosis and treatment of GBM 32 . Several studies have shown that CSF Exo-encapsulated miRNAs can be used to appropriately assess the potential molecular genetic status, drug resistance and prognosis of GBM [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…However, EVs' therapeutic importance in GBMs extends beyond their use as biomarkers, and currently they are beginning to be considered for antitumoral therapy. The therapeutic application takes advantage of the EV ability to cross the blood brain barrier and consists of encapsulating therapeutic cargo in EVs to deliver messages aimed at suppressing oncogenicity of GSCs or inhibiting tumor-supportive actions of microenvironment cells [85]. In addition, knowing the important roles played by EVs in the maintenance of a tumor-supportive environment, in the tumorigenicity of GSCs or even in the induction of malignant transformation, it is logically sound to think that future strategies will be focused in trying to suppress EV biogenesis or EV release by GBM cells.…”
Section: New Perspectivesmentioning
confidence: 99%
“…Also, EVs may be taken up by immune cells, leading to immunosuppression [17]. More recently, EVs have even gained a role in cancer diagnosis and therapy [18][19][20] as biomarker molecules that may be identified in different primary tumors with high sensitivity and specificity [21]. Regarding pancreatic cancer, Kalluri and colleagues found that glypican-1 (GPC1), a cell surface proteoglycan, is specifically enriched in circulating exosomes (30-200 nm endosome-derived EVs).…”
Section: Introductionmentioning
confidence: 99%